Land Use Based on Ecological Aspects in Samangki Village and Bantimurung National Park, Maros Regency - Hadrianti H; Hasriyanti H; Erman Syarif; Ramli Umar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to study ecological aspects related to land use in Samangki Village, Simbang District, Maros District. Qualitative methods are used in this research, with data collection through interviews, field observations, and documentation studies. The results show that Samangki Village has unique ecological characteristics, with natural ecosystems of forests, rivers, and agricultural land. However, there are significant land- use changes due to urbanization factors, government policies, and economic changes. The ecological impacts faced include the decline in soil quality, water, and biodiversity. These findings have important implications for efforts to maintain the sustainability of land use in the Samangki Village. Bisedas that,This research tries to explain the development of Bantimurung Tourism Park. So the uniqueness of the Bantimurung-Bulusaraung National Park that attracts local and foreign tourists, karst: caves with beautiful stalagmites and stalagmites, and is best known as a butterfly. The method used in this study is a research method by collecting data (heuristics) that contains both primary and secondary sources obtained from interviews and the results of the presentation of previous studies, after which an assessment of the sources obtained in order to obtain information that is acceptable and reliable. The data that has been processed are then interpreted into historical narratives, after which they are written in historiography. The results of this study describe Bantimurung which has the potential of natural charm, benefits, and educational value. This development certainly has a significant impact on the economic and socio-cultural community.